2019
DOI: 10.1371/journal.pone.0224697
|View full text |Cite
|
Sign up to set email alerts
|

Video abstracts and plain language summaries are more effective than graphical abstracts and published abstracts

Abstract: BackgroundJournals are trying to make their papers more accessible by creating a variety of research summaries including graphical abstracts, video abstracts, and plain language summaries. It is unknown if individuals with science, science-related, or non-science careers prefer different summaries, which approach is most effective, or even what criteria should be used for judging which approach is most effective. A survey was created to address this gap in our knowledge. Two papers from Nature on similar resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…A recent survey reported that alerts were one of the most preferred update mechanisms for scientists (Bredbenner & Simon, 2019). However, users should be aware of an overwhelming number of alerts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey reported that alerts were one of the most preferred update mechanisms for scientists (Bredbenner & Simon, 2019). However, users should be aware of an overwhelming number of alerts.…”
Section: Resultsmentioning
confidence: 99%
“…However, these conclusions should be considered with caution as there were important study limitations (risk of sampling bias, evaluation of knowledge gain through a small number of question items). A recent survey reported that alerts were one of the most preferred update mechanisms for scientists (Bredbenner & Simon, 2019). However, users should be aware of an overwhelming number of alerts.…”
Section: Resources That Push Informationmentioning
confidence: 99%
“…Recognizing the need to adapt reports of scientific findings to non-expert audiences, including scientists working in other fields of research, many journals, such as eLife, Autism Research, Functional Ecology, Cell, and Science, have started offering plain-language summaries or graphical abstracts and video abstracts (eLife, 2019;Shailes, 2017). As another recent study established, from amongst traditional abstracts, graphical abstracts, video abstracts, and plain-language summaries, the latter two most successfully produced comprehension, a feeling of understanding, and enjoyment (Bredbenner & Simon, 2019). In view of all of the above, it is perhaps not very surprising that a dedicated platform, Kudos (www.growkudos.com/), has been operating since 2014 with the express aim of helping scholars communicate their research in plain language as a means of broadening their reach and impact.…”
Section: Plain-language Summaries Published Along With the Scholarly mentioning
confidence: 99%
“…Plain‐language summary (PLS) is a synopsis of research findings written in an easily understandable way, so that even lay audience would grasp the content 1 . It might be science journalists, healthcare practitioners, academic professionals, policymakers or the general public; they need to understand and engage with the research.…”
Section: Introductionmentioning
confidence: 99%